Farmer Behavior in Cocoa Farming Activities in Gitak Demung Village, Gangga District, North Lombok Regency - Fajriani, Nurdani; Mulyati, Mulyati; Suwardji, Suwardji (Pascasarjana Universitas Mataram, 2024)
The aims of this study is to investigate farmers' behavior in cocoa farming activities in dryland farming in Gitak Demung Subvillage, Village of Gangga, Sub-district of North Lombok District. The research was conducted using surveys and in-depth interviews (FGD) to collect data on the cultivation practices carried out by cocoa farmers and the factors that influence their behavior (How Many Samples were taken). The survey results showed that farmers in Gitak Demung Village have a very good level of behavior, with the majority of farmers implementing good cultivation practices and in accordance with recommendations. In-depth interviews revealed that farmers' knowledge and awareness of good cultivation practices are the main factors influencing their behavior. In addition, adequate access to resources and technology also plays an important role in shaping good farmer behavior. The findings suggest that the extension and education efforts that have been undertaken by the government, agricultural institutions, and related organizations have had a positive impact in improving farmers' behavior. In conclusion, this study concludes that farmers in cocoa farming activities in Gitak Demung sub-village a very good level of behavior, and improvements in farmers' knowledge and access to agricultural resources and technology need to be considered to maintain and improve this good behavior to achieve sustainable agricultural production of cacao